Influence of the genetic background on the reproductive phenotype of mice lacking Cysteine-RIch Secretory Protein 1 (CRISP1) - Weigel Muñoz, Mariana (2018)
Epididymal sperm protein CRISP1 has the ability to both regulate murine CatSper, a key sperm calcium channel, and interact with egg-binding sites during fertilization. In spite of its relevance for sperm function, Crisp1-/- mice are fertile. Considering that phenotypes can be influenced by the genetic background, in the present work mice from the original mixed Crisp1-/- colony (129/SvEv*C57BL/6) were backcrossed onto the C57BL/6 strain for subsequent analysis of their reproductive phenotype. Whereas fertility and fertilization rates of C57BL/6 Crisp1-/- males did not differ from those reported for mice from the mixed background, several sperm functional parameters were clearly affected by the genetic background. Crisp1-/- sperm from the homogeneous background exhibited defects in both the progesterone-induced acrosome reaction and motility not observed in the mixed background, and normal rather than reduced protein tyrosine phosphorylation. Additional studies revealed a significant decrease in sperm hyperactivation as well as in cAMP and protein kinase A (PKA) substrate phosphorylation levels in sperm from both colonies. The finding that exposure of mutant sperm to a cAMP analog and phosphodiesterase inhibitor overcame the sperm functional defects observed in each colony indicated that a common cAMP-PKA signaling defect led to different phenotypes depending on the genetic background. Altogether, ourobservations indicate that the phenotype of CRISP1 null males is modulated by the genetic context and reveal new roles for the protein in both the functional events and signaling pathways associated to capacitation.